Role of Organizational Culture and Implementing the Critical Success Factors Resulting in Reduced Medical Errors from the Viewpoint of Nurses: organizational culture and critical success factors in reducing medical errors - Ghasemi , Morteza; Jarahi , Hosein (Bioethics and Health Law Journal (BHL), 2022)
Background and Aim: A set of management practices called critical success factors and organizational culture can lead to a misplaced program for reaching a goal in the hospital. The incidence of medical errors, one of the most important issues influenced by multiple factors, undermines the quality of healthcare provision and satisfaction and increases costs. Considering that medical errors constitute 44,000-98,000 of the annual deaths in the United States and the lack of reliable statistics in Iran, we aimed to examine the roles of organizational culture and critical success factors in reducing medical errors. Materials and Methods: This applied cross-sectional study was performed among the staff of hospitals affiliated with Arak University of Medical Sciences, Arak, Iran. A 44-item questionnaire was used to collect the data. The questionnaire was designed based on the studies by McFadden, Cameron, and Quinn, and Gowen, and Tallon, the validity and reliability of which were confirmed in this study. Descriptive (frequency distribution) and inferential statistics (ANOVA,two-sample-test, and linear regression) were employed to analyze the data in SPSS, version. Ethical Considerations: The informed consent was obtained from participants after explaining the research aims and the participants were assured about the confidentiality of information. Findings: Most of the respondents were women (58.1%) and within the 30-40 years age group (52.5%). Further, 50.4% of the participants had a Bachelor’s degree. Two main hypotheses and 10 sub-hypotheses were tested and partially accepted. Our results suggested that staff participation, error report, cultural change, education and training, statistical reports, system redesign, collaborative culture, hierarchical culture, mission culture, compatibility culture, and implementation of critical success factors can contribute to reducing errors. Conclusion: Hospital managers must try to encourage the development and maintenance of a culture that emphasizes interpersonal relationships, development of human resources, mentoring co-workers, teamwork and participation, trust, and commitment. To this end, hospital managers should recognize the role of organizational maturity in reducing medical errors and encourage employees to develop organizational culture and increase organizational maturity. *Corresponding Author: Morteza Ghasemi; Email: m-ghasemi@iau-arak.ac.ir; ORCID: https://orcid.org/0000-0002-2142-801X Please cite this article as: Rahbarpour MR. Meaning and Conception of Bioethics and its Realm. Bioeth Health Law J. 2021; 1:1-8 (e20). http://doi.org/10.22037/bhl.v1i1.38178